The effects of taurine ingestion on anaerobic and physiological performance in female rugby players - Bingöl Diedhiou, Azize; Milanović, Zoran; Can Eser, Mustafa; Şahin, Fatma Neşe; Hamlin, Michael; Can Yıldırım, Ulaş (Research in sports medicine, 2024)
The purpose of this study was to investigate the acute effect of low, moderate, or high doses of taurine on anaerobic and physiological performance in female rugby players. A total of 16 sub-elite female rugby athletes (21.3 ± 1.5 yr, 168.0 ± 4.9 cm, 62.1 ± 3.5 kg mean ± SD) participated in this research. Following familiarization, participants attended 4 successive tests separated by 72 h in a randomized, counter-balanced, crossover research design. Following an over night fast, participants completed a 5-min 60 Watt warm-up followed by a 30-s Wingate anaerobic test on a cycle ergometer after ingestion of either 2 g taurine (LOWTAU), 4 g (MODTAU), 6 g (HIGHTAU) or placebo (PLA) 1 h before the test. Peak (PP) and mean power (MP) along with heart rate (HR), rating of perceived exertion (RPE), capillary lactate and blood glucose were measured. LOWTAU did not affect PP, MP, HR, lactate and glucose compared to PLA (p > 0.05), while MODTAU improved MP and HIGHTAU improved PP and MP compared to PLA and LOWTAU (p < 0.05). MODTAU and HIGHTAU had little effect on HR, blood lactate and glucose (p > 0.05). A single dose of taurine (MODTAU or HIGHTAU) 1 h prior to competition or training would provide an ergogenic effect on subsequent power output.
Keywords: Double-Blind Method; krevní glukóza; Humans; tělesná námaha; americký fotbal; Athletic Performance; Physical Exertion; Football; Performance-Enhancing Substances; Dietary Supplements; sportovní výkon; mladý dospělý; Warm-Up Exercise; Taurine; Lactic Acid; potravní doplňky; zahřívací cvičení; látky zvyšující výkon; Blood Glucose; klinické křížové studie; Cross-Over Studies; Anaerobic Threshold; ženské pohlaví; Heart Rate; Exercise Test; lidé; zátěžový test; srdeční frekvence; taurin; kyselina mléčná; Young Adult; anaerobní práh; dvojitá slepá metoda; Female